(untitled) (Al-Academy, 2016)
The technical development has significant effects on the mediator Alcinmatugrave, and TV originated mainly based on technical, with the development and the continuation of these technologies and the enormous impact on the level of the television picture, initially dramas in recent times approaching in the aesthetic composition of the film thanks to the employment of modern digital technologies, Montag was not only one of the cinematic elements that went into television thanks to technical developments analogue and digital, and which added the possibility of large processors in the picture, high-definition digital cameras that have led to dispense often for artificial lighting intensive imaging light available, as these cameras have helped use the corners of filming it was not traditional in the world of television picture because of their small size and lightness, easily and placed anywhere and diversity lenses, and with high-definition imaging feature FULL HD turned most of the home television screens to HD -FULL HD screens -3D sizes widescreen to view natural as , The Voice technology level has become possible to add a wide range of audio tracks amount to hundreds depending on the need of music and effects and dialogue, which sometimes seems closer to a mixture of realism votes as we hear in our daily lives, all of these techniques were used to achieve a sufficient amount of goals The approach of the most aesthetic image, which is why it was felt researcher for the good guys this address